PERSILANGAN GAYA KARAWITAN KARATON KASUNANAN DAN PURA MANGKUNEGARAN - Sosodoro, Bambang (Institut Seni Indoensia Surakarta, 2015)
This research is a field study that examines the karawitan (Javanese music) of Karaton and Mangkunegaran. The selection is based on the material objects of historical reality and the fact of music. It is that they have enough problems as interesting and actual scientific studies to increase the repertoire of Karawitan. Surakarta palace compound and Mangkunegaran are two important pillarssupporting musical identity of Surakarta style. The issue of the Palace and Mangkunegaran Karawitan is an interesting topic to be studied from the various viewpoints. This is because the two kingdoms are at Surakarta style musical territory, but producethe different musical works. Idioms and vocabulariesare working on covering the game Ricikan and gending repertoire.The work of gending between the two are the same but the result of musical taste shows differences. The second issue of the royal musicians is increasingly attractive when the marriage is bond between the Mangkunegaran and Yogyakarta Sultanate.The physical and aesthetic (musical) characteristics are identic between the two. The marriage eventually leds to the musical dance of Yogyakarta style of Mangkunegaran. Although it is said to be identic but on the other hand it is also flowing style of Surakarta. This study aims to reveal the differences and similarities between the music and the dance of KaratonMangkunegaran. The discussionsof the two are limited to the Dance Srimpi. To uncover this needs the use of textual and contextual approaches. Textual studies focus on the shape, form, and elements inherent in the study of arts subjects. The musicians sit as a text to be read and interpreted,and thecontextual approach is used to reveal the factors behind the development and the difference between the two. This topic is important to be examined because the study that focuses on the comparison of dance music between the Palace and Mangkunegaran has never been done.Keywords: Cross culture, karawitan, dance Srimpi, palace, differences and similarities.